The man who knew too little [videorecording (DVD)] - Murray, Bill, 1950 September 21-; Gallagher, Peter, 1955-; Farrar, Robert (Archive collection., 2015)
Wallace Ritchie, an American vacationer in London, doesn't know that the bullets are real and the truth serum true. He thinks the intrigue erupting around him is part of an audience-participation theater event. Yet the world's fate depends on this gullible goofus who can't even spell CIA.